Antimicrobial Potential of Extract from a Pseudomonas aeruginosa Isolate. (29th June 2022) - Amankwah, Francis Kwaku Dzideh; Gbedema, Stephen Yao; Boakye, Yaw Duah; Bayor, Marcel Tunkumgmen; Boamah, Vivian Etsiapah
Abstract : Microorganisms are one of the main sources of antimicrobial agents and over 50% of antibiotics currently used in hospitals are metabolites from microbes. This study aimed to isolate microorganisms from the Dompoase landfill site, Kwame Nkrumah University Physics Garden, Kosiko River, and Ada Foah seashore of Ghana and screen their metabolites for antimicrobial activity. Forty-eight (48) microorganisms were isolated and their metabolites were screened against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae, Vibrio cholerae, Salmonella typhi, Pseudomonas aeruginosa, Streptococcus pyogenes, Proteus mirabilis, and Candida albicans using the agar well diffusion method. Ten (10) of the isolates exhibited antimicrobial activity. Isolate DO5, identified as P. aeruginosa isolate, from the Dompoase landfill site was selected for fermentation because it exhibited the highest activity against all the test organisms. DO5 produced optimum antimicrobial activity when fermented for 11 days at 30°C. In the agar diffusion method, the extract of isolate DO5 recorded zones of inhibition ranging between 11.67 ± 0.23 and 21.50 ± 0.71 mm. The MIC and MBC recorded for the DO5 extract ranged from 3.13–25.0 mg/mL and from 6.25–50.0 mg/mL, respectively. Column chromatography analysis yielded eight (8) subfractions from the DO5 extract. IR analysis revealed the presence of functional groups such as alcohols, esters, and hydrocarbons in the fractions. GC-MS analysis identified nine compounds that have been reported to have antimicrobial agents. The DO5 metabolites stand the chance to be developed into potent antibiotics for infection treatment.